Deck scene on board whaling schooner A.T. Gifford, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1907)
Deck scene on board the whaling schooner A.T. Gifford, Hudson Bay, ca. 1907-1912. Inuit and American crew members can be seen. Dogs, whaleboats and gear are also visible. Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as # 1. The schooner A.T. Gifford was built in 1883 at Essex, Massachusetts. George Comer was her master during one of his Arctic voyages in which he mapped areas in the Hudson Bay area. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.